Isolation and Characterization of Multidrug Resistant Enterobacteriaceae in Urine Sample of Patients Suffering from Urinary Tract Infection with Diabetes and Nephropathy - Ahsan, Nazmul; Rahman, Monzilur; Islam, Md Nazrul; Akhand, Anwarul Azim (Dhaka University Journal of Pharmaceutical Sciences, 2021)
Multidrug-resistant (MDR) organisms are spreading widely and becoming an issue of utmost importance to deal with. In the current study, ten urine samples from diabetic patients suffering from multiple complications, including urinary tract infection (UTI) and nephropathy were investigated. Antibiogram assays of the bacterial isolates from collected samples demonstrated resistance against most of the antibiotics tested. Further studies were conducted to determine the types of resistant bacteria that caused UTI. Analyzing the 16S rDNA sequence and phylogenetic tree, 3 isolates were identified as Escherichia coli, 5 as Klebsiella pneumoniae and the rest 2 as Enterobacter asburiae. The findings of this research indicate the necessity of urgent attention to find an effective alternative drug for treating infections caused by these resistant isolates. Dhaka Univ. J. Pharm. Sci. 20(1): 87-93, 2021 (June)